Innovations in Strategic Finance and Accounting: Insights from Research Centers in a VUCA Environment - Raden Muhammad Syah Arief Atmaja Wijaya; Indrawati Yuhertiana; Diarany Sucahyati; Wilma Cordelia Izaak; Endah Susilowati; Diah Hari Suryaningrum; Ignathia Martha Hendrati; Helmy Wahyu Sukiswo; Condro Widodo; Seftin Fitri Ana Wati; Anindo Saka Fitri (JASF: Journal of Accounting and Strategic Finance, 2024)
This paper examines the function of research centers in promoting strategic innovations in finance and accounting under the VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) paradigm. This work employs a qualitative approach, incorporating benchmarking of research centers and literature evaluation, to identify approaches that improve financial resilience and adaptation. There are three research that develop financial resilience fields from Indonesia, Canada, and the United States that were analyzed. The data was obtained from field benchmarking and website observation. Comparative analysis is used to get a deep understanding of how research centers facilitate the advancement of innovative financial and accounting strategies to tackle challenges in VUCA environments. The results underscore the importance of collaboration, technological integration, and actionable frameworks, providing recommendations for academia, governments, and communities to connect research-driven innovation with practical application. This research highlights the unique role of research centers in addressing VUCA challenges by integrating technology-driven frameworks, data-centric tools, and community-based approaches, offering a comprehensive perspective on bridging theory and practice to enhance financial resilience and adaptability.